PEMASARAN POLITIK CALEG PENDATANG BARU DALAM PEMILU (STUDI KASUS WARDI NINGSIH CALEG PAN DAPIL 1 KABUPATEN LAMANDAU) - Ronny Sanjaya (Politika: Jurnal Ilmu Politik, 2017)
Entering the era of democracy in Indonesia since 1998, impact on the progress of Elections Elections in Indonesia made progress since then, parliamentary elections will directly make the participants prepare a strategy to deal with it. Similarly, participants from District Lamandau. Researchers are searching for a legislative candidate from the district Lamandau newcomers to the dimensions of political marketing. Candidates studied were Wardi Ningsih candidates from the party PAN. This research uses descriptive research. The results of this study are Wardi Ningsih use pull marketing, push marketing, and marketing pass. candidates prepare and deliver a political product with a political marketing approach to deliver its programs to voters.Keywords: Political marketing, Elections, Legislative candidate